Cytomegalovirus Retinitis in Chinese Patients of non-Hodgkin Lymphoma with Normal CD4 Counts - Lan Liu; Yongfeng Xu; Huang, Zhu; Yanhong Chen (International Journal of Medical Research, 2013)
Objective: To manifested the clinic features in two cases of cytomegalovirus(CMV) retinitis in Chinese patients of non-Hodgkin lymphoma with normal CD4 counts. Methods: Two patients with non-Hodgkin lymphoma presented with floaters and vision reduction in affected eyes. The patient underwent eye examination and blood investigation, and vitreous was extracted for CMV-DNA polymerase chain reaction (PCR). The patient was treated with intravenous and intravitreal ganciclovir. Results: Fundoscopy showed typical yellow and white lesions in the retina of affected eyes. Blood investigation showed HIV(-), CMV- IgG (+) IgM (-),and CD4 T-cell counts more than 300 cells/ul. CMV DNA PCR(+) of vitreous sample supported the diagnosis of CMV retinitis. Retinitis regressed after the treatment of ganciclovir. Conclusions: CMV retinitis occurred in non-HIV disease such as non-Hodgkin lymphoma with normal CD4 counts. These cases showed CMV-DNA PCR of vitreous may be a good marker for CMV retinitis and intravitreal ganciclovir may be an effective treatment.